A policy on geometric design of highways and streets, 2018. (American Association of State Highway and Transportation Officials, 2018)
Highway engineers, as designers, strive to meet the needs of highway users while maintaining the integrity of the environment. Unique combinations of design controls and constraints that are often conflicting call for unique design solutions. A Policy on Geometric Design of Highways and Streets provides guidance based on established practices that are supplemented by recent research. This document is also intended as a comprehensive reference manual to assist in administrative, planning, and educational efforts pertaining to design formulation